Developing visual design creativity through online collaborative learning: insights from activity theory / Syamsul Nor Azlan Mohamad ... [et al.] - Mohamad, Syamsul Nor Azlan; Zamri@Zimri, Mohd Taufik; Abdullah, Zaleha; Abu Samah, Norazrena; Mohd Zaid, Norasykin (Universiti Teknologi MARA, Kedah, 2024)
This study investigates the development of social creativity in visual design education through online collaborative learning, using Activity Theory as a framework. The research explores how digital tools, social interactions, and educational structures influence creative processes in an online setting. The study involved a qualitative analysis of collaborative activities among visual design students in a virtual learning environment. Findings indicate that the nature of online tools, the dynamics of the online community, and the distribution of creative tasks play crucial roles in fostering social creativity. The research highlights the importance of well-structured online platforms that promote effective communication, peer feedback, and collaborative problem-solving. It also underscores the need for educational frameworks that integrate these elements into the curriculum. The study contributes to the understanding of how digital environments can enhance creativity in visual design education and offers insights for educators to optimize online collaborative learning. It opens avenues for further research into the use of emerging technologies in creative disciplines and the development of more effective digital education strategies.